DEVELOPMENT IN DEVELOPING COUNTRIES (CASE STUDY: IMPLEMENTATION OF THE INDONESIA-CHINA COOPERATION PROJECT IN THE DEVELOPMENT OF THE JAKARTA-BANDUNG HIGH-SPEED RAILWAY IN 2015–2023): KERJA SAMA PEMBANGUNAN DI NEGARA BERKEMBANG (STUDI KASUS: IMPLEMENTASI PROYEK KERJA SAMA INDONESIA-TIONGKOK DALAM PEMBANGUNAN KERETA CEPAT JAKARTA-BANDUNG TAHUN 2015-2023) - Mahardika, Bagus; Purnawarman, Andi (Journal of Administration and International Development, 2025)
This study aims to understand and describe the project implementation of cooperation between Indonesia and China in the development of the high-speed rail project connecting Jakarta and Bandung. The type of research used in this paper is descriptive, with data sourced from literature, academic readings, and news reports. The data were collected using a literature review technique and analyzed qualitatively based on their relevance to the research problem. This study finds that the Jakarta-Bandung High-Speed Railway project, a collaboration between Indonesia and China, has been effectively implemented through a functional partnership. PT KCIC, a joint consortium between the two countries, was established to manage funding, distribute financing, and serve as the executor of Engineering, Procurement, and Construction (EPC) as well as Operation and Maintenance (O&M). The project reflects mutual interdependence: China provides expertise, technology, and training to support localization and knowledge transfer, while Indonesia contributes land and is responsible for regional development along the rail corridor. This development aims to generate economic benefits that help repay the project’s investment and loans. Overall, the cooperation highlights a balanced division of responsibilities, emphasizing institutional synergy and shared goals in infrastructure modernization and capacity building through the integration of technology and collaborative governance.